2014
DOI: 10.11648/j.edu.20140306.19
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Affecting the Performance of the Principal

Abstract: Absract: This paper describes some of the factors that affect the performance of the principal. Research conducted by the survey, involving a total of 116 persons of Secondary School Principals in Medan, North Sumatra, Indonesia, which was taken by random sampling technique. Data captured with three types of instruments, namely instrument tests, observation sheet and questionnaire which is developed by the researchers. This research is explanatory, which is intended to explain the effect of exogenous variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This finding is proven by the research work of Manullang (2014) that showed that the school heads' organizational commitment is the main factor that directly influences and relates to school performance.As underscored in the study, commitment, determination and the capability to willingly embrace and wholeheartedly accept school as essential part of his school heads' life is the propelling force that influences school performance. Furthermore, the school head has the willingness to perform seriously the job demonstrating responsibility, fidelity and confidence, pride on their work and always mindful and protecting the welfare of the school personnel and, above all, the learners.…”
Section: Correlation Between the Profile And Performance Level Of Ele...mentioning
confidence: 81%
“…This finding is proven by the research work of Manullang (2014) that showed that the school heads' organizational commitment is the main factor that directly influences and relates to school performance.As underscored in the study, commitment, determination and the capability to willingly embrace and wholeheartedly accept school as essential part of his school heads' life is the propelling force that influences school performance. Furthermore, the school head has the willingness to perform seriously the job demonstrating responsibility, fidelity and confidence, pride on their work and always mindful and protecting the welfare of the school personnel and, above all, the learners.…”
Section: Correlation Between the Profile And Performance Level Of Ele...mentioning
confidence: 81%